Writing as a Liberal Art in an Age Neither Artful nor Liberal - Douglas Hesse (Journal of the Assembly for Expanded Perspectives on Learning, 2018)
If the personal essay no longer finds a place in First-Year Composition, how do students learn to make meaningful connections in a fragmented and politically fraught world?